Secure Routing for Multihop Ad Hoc Networks With Inhomogeneous Eavesdropper Clusters - Chen, G; Coon, JP; Tajbakhsh, SE (Institute of Electrical and Electronics Engineers, 2018)
This paper studies finding the secure path according to the secrecy connectivity probability (SCP) in the multihop ad hoc networks in the presence of inhomogeneous eavesdropper clusters. We consider both random and fixed eavesdropper clusters, where the former case assumes that there is no knowledge of the locations of the clusters and the latter case assumes that the locations of the clusters can be estimated accurately. First, we derive the end-to-end SCP to characterize the secrecy performance of a given path in a general multihop wireless network with half-duplex randomize-and-forward relaying. Then, we consider a full-duplex scheme at the legitimate receiver, which receives the useful information while broadcasting a jamming signal to the potential eavesdroppers to further enhance the secrecy connectivity. Then, a novel secure routing algorithm that can provide the maximum SCP for any legitimate transmitter/receiver pair in a distributed manner is proposed. The theoretical analysis is verified by Monte Carlo simulation results. The results show that our secure routing algorithm provides similar results compared to an exhaustive search. For the random eavesdropper cluster case, the optimal route is independent of the knowledge of the cluster, which is the same as the homogeneous eavesdropper case. However, for the case where eavesdropper clusters are fixed and their locations are known a priori, the optimal path selection depends on the radii and locations of the eavesdropper clusters and the average number of eavesdroppers in each cluster.